2023
DOI: 10.7717/peerj.15526
|View full text |Cite
|
Sign up to set email alerts
|

Identifying successful combinations by fertility index in old garden roses and hybrid tea roses crosses

Abstract: The success of rose breeding programs is low due to poor seed sets and germination rates. Determining fertile parents and cross combinations that show high compatibility could increase the effectiveness of breeding programs. In this study, three rose varieties belonging to Rosa × hybrida (Jumilia, First Red and Magnum), and two old garden rose species (Black Rose and Cabbage Rose) with known ploidy levels were reciprocally crossbred under controlled conditions to determine the successful crosses by checking fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Considering that miniature roses with small flower diameters may have less stigma, they had lower seed formation than other modern roses. It has been reported that fruit formation, the number of seeds per fruit, and seed formation are lower in interspecies crosses than that in intraspecies crosses ( Kılıç, 2023 ). Successful results were obtained in fruit formation, the number of seeds per fruit, and seed formation by crossbreeding between species in miniature roses with limited fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that miniature roses with small flower diameters may have less stigma, they had lower seed formation than other modern roses. It has been reported that fruit formation, the number of seeds per fruit, and seed formation are lower in interspecies crosses than that in intraspecies crosses ( Kılıç, 2023 ). Successful results were obtained in fruit formation, the number of seeds per fruit, and seed formation by crossbreeding between species in miniature roses with limited fertility.…”
Section: Discussionmentioning
confidence: 99%
“…All parents were obtained as one-year-old plants from a company in Şanlıurfa. The planting of plants, greenhouse growing conditions, and cultural practices such as irrigation, fertilization, and pest control were carried out following the procedures described by Kılıç (2023).…”
Section: Plant Material Planting the Parents And Cultural Practicesmentioning
confidence: 99%
“…Some modern and old garden roses were found to have at least 3.4 times more stigma than the Black rose (Doğan et al, 2020;Kılıç, 2023). Therefore, in crossbreeding studies involving genotypes with fewer stigmas, the number of seeds is expected to be lower compared with genotypes with more stigmas.…”
Section: C2 C1mentioning
confidence: 99%
See 1 more Smart Citation